Metabolic shift underlies recovery in reversible infantile respiratory chain deficiency. (31st October 2020) - Hathazi, Denisa; Griffin, Helen; Jennings, Matthew J; Giunta, Michele; Powell, Christopher; Pearce, Sarah F; Munro, Benjamin; Wei, Wei; Boczonadi, Veronika; Poulton, Joanna; Pyle, Angela; Calabrese, Claudia; et al.
Abstract: Reversible infantile respiratory chain deficiency (RIRCD) is a rare mitochondrial myopathy leading to severe metabolic disturbances in infants, which recover spontaneously after 6‐months of age. RIRCD is associated with the homoplasmic m.14674T>C mitochondrial DNA mutation; however, only ~ 1/100 carriers develop the disease. We studied 27 affected and 15 unaffected individuals from 19 families and found additional heterozygous mutations in nuclear genes interacting with mt‐tRNAGlu including EARS2 and TRMU in the majority of affected individuals, but not in healthy carriers of m.14674T>C, supporting a digenic inheritance. Our transcriptomic and proteomic analysis of patient muscle suggests a stepwise mechanism where first, the integrated stress response associated with increased FGF21 and GDF15 expression enhances the metabolism modulated by serine biosynthesis, one carbon metabolism, TCA lipid oxidation and amino acid availability, while in the second step mTOR activation leads to increased mitochondrial biogenesis. Our data suggest that the spontaneous recovery in infants with digenic mutations may be modulated by the above described changes. Similar mechanisms may explain the variable penetrance and tissue specificity of other mtDNA mutations and highlight the potential role of amino acids in improving mitochondrial disease. Abstract : Heterozygous mutations in nuclear genes interacting with mt‐tRNAGlu induce the integrated stress response and metabolic rearrangements, reducing penetrance and promoting spontaneous recovery in a rare mitochondrial myopathy. Synopsis: Reversible infantile respiratory chain deficiency (RIRCD) is a rare mitochondrial myopathy associated with homoplasmic mutation in mt‐tRNAGlu. Heterozygous mutations in nuclear genes interacting with mt‐tRNAGlu induce the integrated stress response (ISR) and metabolic rearrangements that reduce penetrance and promote spontaneous RIRCD recovery in infants. Nuclear gene variants that affect glutamate/glutamine metabolism or mt‐tRNAGlu aminoacylation contribute to manifestation of RIRCD, when co‐occurring with the mtDNA m.14674T>C variant. Analysis of diseased muscles reveals that recovery from RIRCD occurs in a stepwise manner in infants. During phase one, ISR signaling increases FGF21 and GDF15 expression and enhances lipid and amino acid metabolism. In a second phase, patients present activation of mTOR, leading to increased mitochondrial biogenesis. ISR and increased mitochondria number facilitate a metabolic shift that improves amino acid availability and contribute to the spontaneous recovery in phase three.